2022
DOI: 10.3389/fphys.2022.884447
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of P450 Genes Enhances Susceptibility to Indoxacarb and Alters Physiology and Development of Fall Armyworm, Spodoptera frugipreda (Lepidoptera: Noctuidae)

Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), is a pest of many important crops globally. Effective control is challenging, with the pest exhibiting resistance to different synthetic pesticides across various groups. However, the mechanisms employed by resistant insects for overexpression of relevant detoxification genes remain unclear. The activity of detoxification enzymes was investigated in this study. Additionally, using RNA interference (RNAi), a functional analysis was completed of two P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 97 publications
1
8
0
Order By: Relevance
“…Similarly, it has been reported that the midgut fat bodies and Malpighian tubules are frequently associated with higher P450 activity ( Hu et al., 2014 ;). In addition, the midgut is a highly crucial organ in the process of detoxification, and the genes that code for the detoxification enzymes involved in this process are frequently highly regulated in this organ ( Feyereisen, 2006a ; Hafeez et al., 2022 ). In this study, we investigated the expression profile of CYP302A1 in different tissues and developmental stages of S. frugiperda by quantitative RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been reported that the midgut fat bodies and Malpighian tubules are frequently associated with higher P450 activity ( Hu et al., 2014 ;). In addition, the midgut is a highly crucial organ in the process of detoxification, and the genes that code for the detoxification enzymes involved in this process are frequently highly regulated in this organ ( Feyereisen, 2006a ; Hafeez et al., 2022 ). In this study, we investigated the expression profile of CYP302A1 in different tissues and developmental stages of S. frugiperda by quantitative RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the droplet-feeding method for RNAi to prevent damage to S. frugiperda larvae as previously defined by ( Wang et al., 2018b ; Hafeez et al., 2022 ). The dsRNA was first diluted (250 μg/μL total volume of 500μL) in diethylpyrocarbonate (DEPC)-treated water before dsRNA feeding experiments.…”
Section: Insect Rearing and Host Plant Selectionmentioning
confidence: 99%
“…Sublethal and transgenerational effects of spirotetramat affected developmental physiology, indicating the role of sublethal concentrations in larval growth, development, and sensitivity to spirotetramat. In previous studies, Physiological and biochemical studies have shown that P450 enzymes are vital to in insect hormone metabolism pathways but details of the molecular processes remain unknown ( Iga and Kataoka, 2012 ; Hafeez et al, 2022 ). The growth and developmental physiology of B. brassicae was hindered after being treated with sublethal concentrations of spirotetramat, but how these sublethal concentrations regulate this process requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their central function in pesticide metabolism, cytochrome P450s are frequently implicated in the development of insect resistance to these chemicals ( Guo et al, 2012 ; Panini et al, 2016 ). One of the most prevalent processes by which insect pests develop resistance to synthetic insecticides is the upregulation of certain detoxifying P450 enzymes within the insect ( Nelson, 2011 ; Hafeez et al, 2022a ; Luo et al, 2022 ). Because of this, insecticide resistance may develop as a result of changes in the activity of detoxifying enzymes in insects in response to exposure to pesticides.…”
Section: Resistance In Invasive Insectsmentioning
confidence: 99%
“…Because of this, insecticide resistance may develop as a result of changes in the activity of detoxifying enzymes in insects in response to exposure to pesticides. Many insect orders, including Coleoptera, Diptera, Hemiptera, Hymenoptera, and Lepidoptera, have shown evidence of P450 overexpression leading to increased resistance to pesticides ( Bass et al, 2011 ; Johnson et al, 2012 ; Liang et al, 2015 ; Wang et al, 2015 ; Chen et al, 2017 ; Khan et al, 2021a ; Khan et al, 2021c ; Hafeez et al, 2022a ; Siddiqui et al, 2022b ).…”
Section: Resistance In Invasive Insectsmentioning
confidence: 99%